Root rot a silent alfalfa killer in China: Distribution, fungal, and oomycete pathogens, impact of climatic factors and its management - Abbas, Aqleem; Mubeen, Mustansar; Sohail, Muhammad Aamir; Solanki, Manoj Kumar; Hussain, Babar; Nosheen, Shaista; Kashyap, Brijendra Kumar; Zhou, Lei; Fang, Xiangling (Frontiers in Microbiology, 2022)
Alfalfa plays a significant role in the pasture ecosystems of China's north, northeast, and northwest regions. It is an excellent forage for livestock, improves soil structure, prevents soil erosion, and has ecological benefits. Presently root rot is a significant threat to the productivity of alfalfa because of the survival of the pathogens as soil-borne and because of lack of microbial competition in the impoverished nutrient-deficient soils and resistant cultivars. Furthermore, these regions' extreme ecological and environmental conditions predispose alfalfa to root rot. Moisture and temperature, in particular, have a considerable impact on the severity of root rot. Pathogens such as Fusarium spp. and Rhizoctonia solani are predominant, frequently isolated, and of major concern. These pathogens work together as disease complexes, so finding a host genotype resistant to disease complexes is challenging. Approaches to root rot control in these regions include mostly fungicides treatments and cultural practices and very few reports on the usage of biological control agents (BCAs). As seed treatment, fungicides such as carbendazim are frequently used to combat root rot; however, resistance to fungicides has arisen. However, breeding and transgenic approaches could be more efficient and sustainable long-term control strategies, especially if resistance to disease complexes may be identified. Yet, research in China is mainly limited to field investigation and disease resistance evaluation. In this review, we describe climatic conditions of pastoral regions and the role of alfalfa therein and challenges of root rot, the distribution of root rot in the world and China, and the impact of root rot pathogens on alfalfa in particular R. solani and Fusarium spp., influences of climatic changes on root rot and summarize to date disease management approach.